Pengaruh Faktor Makroekonomi terhadap Return Saham pada Perusahaan Manufaktur PT Barito Pascific Periode 2015-2024 - Ulfa Hakiki Annur; Nurman Nurman; Rezky Amalia Hamka; Anwar Anwar; Abdul Rahman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to determine the partial and simultaneous effects of macroeconomic factors on stock returns at the manufacturing company PT Barito Pacific for the period 2015–2024. The macroeconomic factors used in this study include interest rates, inflation, and exchange rates, as these three variables are economic indicators frequently associated with fluctuations in stock returns. This study employs a quantitative approach using a documentary method. The population consists of all quarterly data from PT Barito Pacific for the period 2015–2024. Sampling was conducted using saturated sampling, in which the entire population was included as the study sample, comprising 40 quarterly data points. Multiple linear regression analysis was performed using SPSS Statistics 2025. The results indicate that, when analyzed individually, interest rates have a positive but insignificant effect, inflation has a negative but insignificant effect, and the exchange rate has a negative and significant effect on stock returns. However, when analyzed simultaneously, interest rates, inflation, and the exchange rate do not have a significant effect on the stock returns of the manufacturing company PT Barito Pacific for the period 2015–2024. It is hoped that the results of this study can serve as a reference for investors and future researchers in understanding the relationship between macroeconomic factors and stock returns.